2021
DOI: 10.12944/carj.9.1.07
|View full text |Cite
|
Sign up to set email alerts
|

Virulence of Five Isolates of Indigenous Beauveria Bassiana Against Eggs and Nymphs of Bemisia Tabaci Gennadius (Hemiptera: Aleyrodidae)

Abstract: This research aims to study the virulence of five isolates of Beauveria bassiana to eggs and nymphs of Bemisia tabaci on tomato. In the experiment eggs and second instar nymphs of B. Tabaci were used. Five isolates of the fungus, i.e., WS, TD312, PD114, PA221, PB211, were tested. Conidial concentration of B. bassiana used were 108 conidia/ml. Experimental parameters included mortality of eggs and nymph and percentage of adult emergence. The results showed that all B. bassiana isolates tested were able to k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…The BbWS isolate, obtained from the stink bug in the same order as BPH (Hemiptera) or from Leptocorisa oratorius (Fabricius) in the same order as the source isolate used, was noted for its efficacy. Flawerina (2021) reported that the BbWS isolate displayed the highest virulence against eggs and instar 2 nymphs of Bemisia tabaci (Gennadius). Isolates B. bassiana originating from the same order as the test insect showed higher virulence compared to isolates from plants (endophytes).…”
Section: Effect Of B Bassiana On Nymph Mortality and Fecundity Of Bphmentioning
confidence: 99%
See 1 more Smart Citation
“…The BbWS isolate, obtained from the stink bug in the same order as BPH (Hemiptera) or from Leptocorisa oratorius (Fabricius) in the same order as the source isolate used, was noted for its efficacy. Flawerina (2021) reported that the BbWS isolate displayed the highest virulence against eggs and instar 2 nymphs of Bemisia tabaci (Gennadius). Isolates B. bassiana originating from the same order as the test insect showed higher virulence compared to isolates from plants (endophytes).…”
Section: Effect Of B Bassiana On Nymph Mortality and Fecundity Of Bphmentioning
confidence: 99%
“…In addition to its role as an entomopathogen, B. bassiana exhibits endophytic behavior in various plant species, colonising plant tissues. Its presence within plants adversely affects insects, particularly plant pests, thereby enhancing plant resistance against pest attacks (Vega 2008;Jia et al 2013;Trizelia et al 2020;Flawerina 2021 The presence of the fungus in corn plants can lead to an 85% reduction in Ostrinia furnacalis (Guenee) larvae, decreasing both the number and length of larval tunnels. Larval mortality is attributed to secondary metabolites such as proline and polyphenol oxidase present in corn plants, which are toxic to larvae.…”
Section: Introductionmentioning
confidence: 99%